Is physiological glucocorticoid replacement important in children?. Issue 2 (31st August 2016) - Porter, John; Blair, Joanne; Ross, Richard J
Abstract : Cortisol has a distinct circadian rhythm with low concentrations at night, rising in the early hours of the morning, peaking on waking and declining over the day to low concentrations in the evening. Loss of this circadian rhythm, as seen in jetlag and shift work, is associated with fatigue in the short term and diabetes and obesity in the medium to long term. Patients with adrenal insufficiency on current glucocorticoid replacement with hydrocortisone have unphysiological cortisol concentrations being low on waking and high after each dose of hydrocortisone. Patients with adrenal insufficiency complain of fatigue, a poor quality of life and there is evidence of poor health outcomes including obesity potentially related to glucocorticoid replacement. New technologies are being developed that deliver more physiological glucocorticoid replacement including hydrocortisone by subcutaneous pump, Plenadren, a once-daily modified-release hydrocortisone and Chronocort, a delayed and sustained absorption hydrocortisone formulation that replicates the overnight profile of cortisol. In this review, we summarise the evidence regarding physiological glucocorticoid replacement with a focus on relevance to paediatrics.